Analysis of the Effect of Compressor Washing on the Inter Turbine Temperature (ITT) Margin of the PW127 Engine - Gunarso Priambudi; Ali Rosyidin (Global Writing Academica Researching and Publishing, 2026)
Aircraft engine performance and reliability are critical factors in ensuring flight safety and operational efficiency. One of the key parameters used to assess the condition of the Pratt & Whitney PW127M turboprop engine is the Inter-Turbine Temperature (ITT) Margin, which represents the available temperature margin relative to the maximum allowable limit. A reduction in ITT Margin generally indicates a decrease in thermal efficiency, often caused by compressor contamination. This study aims to analyze the effect of compressor washing on the ITT Margin of PW127M engines installed on ATR 72-600 aircraft. The research was conducted on ten PW127M engine units operated by PT Wings Abadi Airlines over a four-month observation period, consisting of two months before and two months after compressor washing. Data were collected from the EMRO system, engine logbooks, and Engine Condition Trend Monitoring (ECTM) reports. The analysis employed descriptive statistical methods and a paired sample t-test to evaluate the significance of ITT Margin changes. The results show that all engines experienced an increase in ITT Margin after compressor washing, with an average improvement of 4.9 °C. Statistical testing produced a t-value of 7.10 and a p-value of 0.0000568 (<0.05), indicating a statistically significant difference. These findings confirm that compressor washing is effective in improving engine thermal performance and should be considered an integral part of condition-based maintenance strategies.